Parathyroid Surgery in the Elderly - Morris, Lilah F. (AlphaMed Press, 2010)
INTRODUCTION. The prevalence of primary hyperparathyroidism (PHPT) is expected to increase in developed nations as the aged population grows. This review discusses issues related to PHPT in the elderly population with a focus on differences in disease presentation, medical and surgical management, and outcomes. METHODS. Literature review of English-language studies of PHPT or parathyroidectomy (PTx) in the elderly was performed. Surgical literature reviewed included original clinical studies published after 1990. Priority was given to studies with >30 patients where institutional practice and outcomes have not changed significantly over time. RESULTS. Elderly patients primarily present with nonclassic symptoms of PHPT that can sometimes be missed in favor of other diagnoses. They have equivalent surgical outcomes, including morbidity, mortality, and cure rates, compared with younger patients, although their length of hospital stay is significantly longer. Several recent studies demonstrate the safety and efficacy of outpatient, minimally invasive parathyroidectomy in an elderly population. Patients are referred for PTx less frequently with each advancing decade, although surgical referral patterns have increased over time in centers that offer minimally invasive parathyroidectomy. Elderly patients experience increased fracture-free survival after PTx. The majority of elderly patients report symptomatic relief postoperatively. CONCLUSION. PTx can offer elderly patients with PHPT improved quality of life. PTx is safe and effective in elderly patients, and advanced age alone should not deter surgical referral.